Grandparents, Parents, Children, and Grandchildren: A Generational Analysis of Sacramental Practices in Ayaviri - Cabala Banda, Pamela (2009)
A generational analysis of Catholic religious practices allows us to better understand the various pastoral approaches applied in the last five decades in an important town in the southern Andes: Ayaviri, capital of the province of Melgar, Puno region. Based on a significant number of surveys obtained by statistical sampling and interviews collected from the inhabitants of the area, this article offers updated information on the sacramental practices -specifically baptism, first communion, confirmation and marriage- of the Andean religion in the area.